Antiproliferative Activity and Molecular Docking Analyses of Sesquiterpene Lactones Obtained from Activity-Directed Isolation of Centaurea saligna (K.Koch) Wagenitz in Neoplastic Cells - Yildirim, Aybeniz; Sen, Ali; Goktas, Bunyamin; Uslu, Harun; Ozakpinar, ozlem Bingol; Bitis, Leyla (Springernature, 2025)
Secondary metabolites obtained from plants are among the most commonly encountered chemotherapeutics used in cancer treatment. Plants contain thousands of metabolites; therefore, it is important to reach the compound primarily responsible for activity by fractionating plant extracts through activity-guided isolation. The cytotoxic activities of C. saligna fractions, sub-fractions, and all pure compounds obtained from the plant were investigated in vitro using MCF-7 (human breast cancer), HeLa (human cervical cancer), and PC-3 (prostate cancer) cell lines. Eighteen compounds were isolated from C. saligna, comprising eight sesquiterpene lactones, three flavonoids, five lignans, and two phenolic compounds, with their structures elucidated through 1H-NMR, 13C-NMR, and HMBC spectroscopic techniques. The molecular docking scores of the pure compounds obtained from these sub-fractions were determined using both AutoDock and AutoDock Vina programs. It has been proven that the affinities of linichlorin B and aguerin B for Bcl-2 are higher than those of other compounds, considering the calculated Ki values and placement scores. Notable activities of linichlorin B, cynaropicrin, and aguerin B (with IC50 values of 13.67 mu g/ml, 6.79 mu g/ml, and 3.46 mu g/ml, respectively) were detected in the PC-3 cell line; aguerin B demonstrated activity most comparable to the standard anticancer agent doxorubicin. Likewise, linichlorin B, aguerin B, and cynaropicrin demonstrated notable efficacy in the HeLa and MCF-7 cell lines, as reported by the American National Cancer Institute. Aguerin B, linichlorin B, and cynaropicrin are projected to serve as promising novel chemotherapeutic agents for cancer therapy.
Keywords: Centaurea saligna; Cytotoxicity; Flavonoids; Sesquiterpene lactones